An Integrated Pain Team Model: Impact on Pain-Related Outcomes and Opioid Misuse in Patients with Chronic Pain. Issue 9 (25th February 2020) - Gibson, Carolyn J; Grasso, Joseph; Li, Yongmei; Purcell, Natalie; Tighe, Jennifer; Zamora, Kara; Nicosia, Francesca; Seal, Karen H
Abstract: Objective: Biopsychosocial integrated pain team (IPT) care models are being implemented in Veterans Health Administration (VA) and other health care systems to address chronic pain and reduce risks related to long-term opioid therapy, with little evaluation of effectiveness to date. We examined whether IPT improves self-reported pain-related outcomes and opioid misuse. Design: Single-group quality improvement study. Setting: Large VA health care system. Subjects: Veterans with chronic pain (N = 99, 84% male, mean age [SD] = 60 [13] years). Methods: Using paired t tests and Wilcoxon matched-pairs signed-ranks tests, we examined pain experience (Brief Pain Inventory, Pain Catastrophizing Scale), opioid misuse (Current Opioid Misuse Measure), treatment satisfaction (Pain Treatment Satisfaction Scale), and pain management strategies among patients with chronic pain before and after three or more IPT encounters. Results: After an average (SD) of 14.3 (9) weeks engaged in IPT, patients reported improvement in pain interference (mean [SD] = 46.0 [15.9] vs 40.5 [16.2], P < 0.001), pain catastrophizing (mean [SD] = 22.9 [13.0] vs 19.3 [14.1], P = 0.01), treatment satisfaction (i.e., "very satisfied" = 13.1% at baseline vs 25.3% at follow-up, P = 0.01), and reduced opioid misuse (mean [SD] = 11.0 [7.5] vs 8.2 [6.1], P = 0.01). Patients reported increased use of integrative (i.e., acupuncture, 11% at baseline vs 26% at follow-up, P < 0.01) and active pain management strategies (i.e., exercise, 8% at baseline vs 16% at follow-up, P < 0.01) and were less likely to use only pharmacological pain management strategies after IPT engagement (19% at baseline vs 5% at follow-up, P < 0.01). Conclusions: Biopsychosocial, integrated pain care may improve patient-centered outcomes related to opioid misuse and the subjective experience and nonpharmacological self-management of chronic pain.